2011
DOI: 10.1253/circj.cj-10-0690
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Respiratory Variation of Inferior Vena Cava Diameter for Estimation of Elevated Central Venous Pressure in Children With Cardiovascular Disease

Abstract: Background:The purpose of the present study was to determine the relationship of inferior vena cava diameter (IVCD) and its respirophasic variation (IVC collapsibility index: IVCCI) with central venous pressure (CVP), and thereby to provide reference cut-offs for such IVC parameters to estimate elevation in CVP in pediatric patients with cardiovascular disease. Methods and Results:The study involved consecutive pediatric patients (n=118) with various heart diseases who either had a central venous catheter in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 21 publications
2
19
0
Order By: Relevance
“…It is unlikely that the present patients were dehydrated because cardiac output and IVCD were preserved, as shown in Table 1. The present relatively low RAP further supports the existing data in Japanese children with congenital heart disease reported by Iwamoto et al 2 A lower RAP compared with Western populations 3,6,12 might be one of the characteristics of …”
Section: Discussionsupporting
confidence: 91%
“…It is unlikely that the present patients were dehydrated because cardiac output and IVCD were preserved, as shown in Table 1. The present relatively low RAP further supports the existing data in Japanese children with congenital heart disease reported by Iwamoto et al 2 A lower RAP compared with Western populations 3,6,12 might be one of the characteristics of …”
Section: Discussionsupporting
confidence: 91%
“…We did not standardize the ventilatory setting during the measurements, and this could have, to some extent, contributed to the variations in the data of mechanically ventilated patients. 1 On the other hand, we had found in our preliminary study that increasing the PIP over 20 mmHg, to maximize cardiopulmonary interaction, minimally affected IVCCI regardless of CVP level. This is also consistent with data reported by Dr Moretti and coworkers, 2 suggesting a significant overlap in the CVP -IVCCI relationship even under the standardized ventilatory setting (data in Table 1 of their paper); the mean IVCCI under the standardized ventilatory setting with PEEP of 0 mmHg and tidal volume of 8 ml/kg was very low and a difference of 6% in IVCCI corresponds to a difference in only 2 mmHg of CVP.…”
mentioning
confidence: 59%
“…In a recent study, Iwamoto et al found a good correlation between the ultrasonographic measurement of the respiratory variation of the inferior vena cava diameter (IVCD) and central venous pressure (CVP) in spontaneously breathing children with hearth disease, but could not find the same correlation in mechanically ventilated patients. 1 Following this observations, it is worth pointing out our interest towards 2 basic concepts of the use of the IVCD and its derived variables.…”
Section: To the Editormentioning
confidence: 86%
“…In order to amplify cardiopulmonary interactions, regardless of the baseline ventilation setting, measurements of arterial waveformderived variables tend to be taken with a positive endexpiratory pressure of ≤5 cmH2O and a tidal volume of 8-10 ml/kg. 2 A similar protocol has been proposed in studies where the IVCD respiratory variation was examined as a preload index, 3 whereas the ventilation parameters were not mentioned by Iwamoto et al 1 Furthermore, intrathoracic pressure variations during the respiratory cycle are strictly dependent on the compliance of the respiratory system: the higher the compliance, as in most pediatric patients, the higher the intrathoracic pressure and the hemodynamic effects of ventilation. 4 2.…”
Section: To the Editormentioning
confidence: 99%